A REVIEW OF PHYTOPHTHORA MEGARKAYA IN COCOA PRODUCTION AND THE RESISTANCE OF COCOA AGAINST THE PATHOGEN - Olaomi, Adeyemi Afeez; Suleiman, Mohammed Nasirudeen; Alege, Gbenga; Odewale, Gbolabo (FUDMA Journal of Sciences, 2026)
Cocoa (Theobroma cacao L.) is an important tropical crop with production limited by black pod disease caused by Phytophthora megakarya in West and Central Africa. Here, we review the biology, infection process, environmental interactions, and pathogenic variability of Phytophthora megakarya, and the resistance mechanisms of cocoa to this pathogen. The life cycle of Phytophthora megakarya involves fast asexual reproduction, formation of motile zoospores, and survival in the form of chlamydospores, which allows the pathogen to persist and spread over long distances in humid conditions. Environmental factors such as high rainfall, temperature, and canopy density affect disease development, while genetic variability within populations of Phytophthora megakarya complicates disease management by increasing virulence and adaptability. The review also points out that host resistance is a possible sustainable control strategy and that it is quantitative and polygenic; cocoa resistance is a multilayered process that includes genetic, morphological, biochemical, and physiological mechanisms such as activation of defense-related enzymes, accumulation of phenolic compounds, and structural barriers such as thicker pod husks. Tolerant cocoa varieties have been bred using advances in molecular breeding and identification of resistance-associated traits, but pathogen diversity and environmental effects can limit the durability of resistance. The study emphasizes that host resistance must be combined with cultural and environmentally friendly management practices for effective and sustainable control of black pod disease in cocoa production systems.